Determining the Impact of Socio-Demographic Variables and Morbid Conditions on General Health Component of Perceived Health Using SF-36 Form - Atul Kumar Singh (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
Perceived health (PH) is a personal evaluation of one’s health and is a powerful, independent predictor of morbidity and mortality. It encompasses so many elements that are challenging to diagnose clinically, like incipient disease, physiological reserves, and psychological reserves. Perceived health status of the 1130 patients was assessed by the general health (GH) dimension of the physical component summary of PH using the 36-Items short form Health Survey (SF-36). In this study we assessed the impact of diabetes mellitus (DM), hypertension (HTN), co-morbidity and other associated factors on the general health dimension of the PH of the patients attending the Outpatient Department (OPD), Inpatient Department (IPD) of Rural Health Training Centre (RHTC) and Urban Health Training Centre (UHTC) running under Shri Ram Murti Smarak Institute of Medical Sciences (SRMS IMS), Bareilly, Uttar Pradesh. It was observed that the impact of morbidity deteriorate the GH score but hypertensive patients scored poor results as compared to those with DM and co-morbid patients (p>0.05). Age was inversely significant to GH scores, but male gender, higher education (p<0.05), and a good occupation were all positively related to GH scores. The geographical area of the study participants had little influence on the GH scores, but urban areas scored slightly higher, but the association was statistically insignificant (p>0.05). Thus young male patients from urban area, educated and having good job had better score for GH and association was statistically significant for education and occupation of the study subjects. The presence of morbidity and co-morbid conditions reduces the patients’ GH. The study also revealed the influence of various socio-demographic factors on PH status.